2015
DOI: 10.1111/sbr.12116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of body position on sleep architecture and quality in subsyndromal adults without apparent obstructive sleep apnea

Abstract: There is a well-known relationship between sleep quality and body position during sleep in patients with obstructive sleep apnea (OSA). In this study, we aimed to investigate the effects of body position on sleep architecture and sleep quality in subjects without sleep apnea. One hundred and one subjects between 24 and 77 years of age, who had undergone polysomnography and had a respiratory disturbance index (RDI) below 5 were included in the study. Sleep stages and sleep parameters in the right, left, supine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Kutbay et al study showed that the AHI (activity apnea-hypopnea index) and average minimum oxygen saturation (SOP) were significantly lower in supine than those in other lying positions, and the heart rate as well as average awakening index were higher [ 17 ]. George et al found that lying on either side can significantly reduce OSA (obstructed sleep apnea) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kutbay et al study showed that the AHI (activity apnea-hypopnea index) and average minimum oxygen saturation (SOP) were significantly lower in supine than those in other lying positions, and the heart rate as well as average awakening index were higher [ 17 ]. George et al found that lying on either side can significantly reduce OSA (obstructed sleep apnea) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The status of airflow dominance between the right and left nasal airways is correlated with sympathetic and parasympathetic dominant states, respectively, as regulated by the ANS, 53,54 the lateralised ultradian rhythm of alternating cerebral hemispheric dominance 55,56 and is tightly coupled to sleep staging 44,46,53,55,57,58 and sleep position. 59 This suggests that the nasal cycle is strongly connected with sympathovagal balance. Nasal-applied continuous positive airway pressure (n-CPAP) is considered the gold standard of OSA treatment but has also been shown to abolish the nasal cycle in awake volunteers.…”
Section: Nasal Cycle and The Autonomic Nervous Systemmentioning
confidence: 99%